2023
DOI: 10.1038/s41392-023-01628-9
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in human central nervous system diseases: a frontier for new therapies

Alexei Verkhratsky,
Arthur Butt,
Baoman Li
et al.

Abstract: Astroglia are a broad class of neural parenchymal cells primarily dedicated to homoeostasis and defence of the central nervous system (CNS). Astroglia contribute to the pathophysiology of all neurological and neuropsychiatric disorders in ways that can be either beneficial or detrimental to disorder outcome. Pathophysiological changes in astroglia can be primary or secondary and can result in gain or loss of functions. Astroglia respond to external, non-cell autonomous signals associated with any form of CNS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 657 publications
3
19
0
Order By: Relevance
“…4,5 An increase in GFAP levels does not always reflect pathology and can be observed after different physiological stimulation such as enriched environment and physical activity. 1 In fact, it has been suggested that a heterogeneous population of reactive astrocytes exists, varying among distinct brain regions with specific responses to differing pathologies. 5−7 Thus, identifying new biomarkers, beyond GFAP, is crucial for capturing the full picture of reactive astrogliosis and improving our understanding of astrocytic heterogeneity in AD.…”
Section: Respectively)mentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 An increase in GFAP levels does not always reflect pathology and can be observed after different physiological stimulation such as enriched environment and physical activity. 1 In fact, it has been suggested that a heterogeneous population of reactive astrocytes exists, varying among distinct brain regions with specific responses to differing pathologies. 5−7 Thus, identifying new biomarkers, beyond GFAP, is crucial for capturing the full picture of reactive astrogliosis and improving our understanding of astrocytic heterogeneity in AD.…”
Section: Respectively)mentioning
confidence: 99%
“…It might be challenging to measure early reactive astrocytes in brain and, for years, increased glial fibrillary acidic protein (GFAP) immunoreactivity in postmortem tissue has been used as a general marker for reactive astrogliosis . However, recent evidence in biomarker research indicates that the potential to represent the whole population of reactive astrocytes in the human brain may be lost if testing is confined to changes in GFAP levels. , An increase in GFAP levels does not always reflect pathology and can be observed after different physiological stimulation such as enriched environment and physical activity . In fact, it has been suggested that a heterogeneous population of reactive astrocytes exists, varying among distinct brain regions with specific responses to differing pathologies. Thus, identifying new biomarkers, beyond GFAP, is crucial for capturing the full picture of reactive astrogliosis and improving our understanding of astrocytic heterogeneity in AD .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13] Brain lesions trigger reactive astrogliosis which, together with microgliosis and reactive remodeling of oligodendrocyte precursor cells, represents evolutionary conserved defensive response aimed at protection and postlesional restoration of the nervous tissue from various forms of pathological stressors and insults. 14,15 Reactive astrogliosis proceeds through complex, still poorly understood, reorganization of astrocytic biochemistry, morphology, and physiology to create multiple contexts-and disease-specific reactive phenotypes. 16,17 Reactive astrogliosis is linked to the activation of several cellular programs and second messenger signaling pathways 15,18 that await to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%